Integration of Islamic Education Values in The Qur’an with the 7 Habits of Great Indonesian Children Program: Tafsir Tarbawi Approach - Masnida, Masnida (Indo-MathEdu Intellectuals Journal, 2026)
Character education plays a crucial role in addressing moral and social challenges in contemporary Indonesia. The 7 Habits of Great Indonesian Children program, which includes waking up early, enjoying worship, exercising regularly, consuming healthy and nutritious food, enjoying learning, engaging in social interaction, and going to bed early, represents a practical effort to instill positive values from an early age. This study aims to examine the relevance of the program and its integration with Islamic educational values using a tarbawi interpretation approach. The research employs a qualitative literature study with content analysis of Qur’anic verses and classical and contemporary tafsir sources related to education and character formation. The findings indicate that the seven habits are consistent with the teachings of the Qur’an and Sunnah, which emphasize moral integrity, discipline, balance, and social responsibility. Integrating Qur’anic values into this program can strengthen the implementation of character education in family, school, and community settings. Therefore, the program has the potential to contribute to the development of Indonesian children who are not only competent in worldly affairs but also possess character and behavior aligned with Islamic values.